Keadilan Sosial Sebagai Tujuan Maqasid Al-Syari’ah dalam Masyarakat Kontemporer - Salsabila, Fitria; Ilmi, Sholihah Samrotul (Interdisciplinary Explorations in Research Journal, 2026)
Social justice is one of the fundamental values (main principles) in Islamic teachings which is in line with the main purpose of establishing Islamic law. Maqasid al-shari'ah aims to realize human benefits and prevent various forms of social damage. In the context of contemporary society faced with the problems of economic inequality, discrimination, structural injustice, as well as the dynamics of globalization and rapid social change, the concept of maqasid is becoming increasingly urgent to be studied. This article aims to analyze the concept of social justice in the perspective of maqasid al-shari'ah as well as its relevance in the reform of contemporary Islamic law by highlighting Jasser Auda's thinking that offers a systems approach in the development of maqasid. The research method used is a literature study with a normative-philosophical qualitative approach through the analysis of relevant literature and legal documents. The results of the study show that Maqaṣid al-Sharia is not only normative-theological, but also applicable and contextual in responding to modern social and legal challenges. The reformulation of maqaṣid initiated by Jasser Auda emphasizes aspects of human resource development, human rights protection, and the character of the Islamic legal system that is holistic, open, multidimensional, and oriented towards the goal of benefit. The application of maqāṣid in the field of family law and sharia economic law shows that Islamic law can be more just, moderate, humanistic, and responsive to the needs of contemporary society.